PENGOLAHAN CITRA AQUA MODIS UNTUK PEMBUATAN PETA ZONA TANGKAPAN IKAN PERAIRAN MUARA KINTAP KALIMANTAN SELATAN - Sobatnu, Ferry; Irawan, Faris Ade (P3M Politeknik Negeri Banjarmasin, 2022)
This research utilizes Sea Surface Temperature from the Aqua MODIS image acquisition in 2018 in identifying potential areas fish catch zone. The purpose of the study was to prove the remote sensing technology digital image processing method for making sea surface temperature maps tested with survey data in the field hot spot productivity Fishing Ground 2015. The Surface Grids System method is a structure matrix used for recording relations the topology contained between data points implicitly. Utilization Surfer software as a means of digital data conversion process raster image into a metric vector data. This technique aims to analyse spatial objects based on area (boundary). Spatial Analysis with overlay technique visualizes the selected zone in isoline at 29.5°C - 31°C. This empirical evidence is used as a reference for making maps from January to June 2018. Based on spatial analysis, fish catch zones in March, April and May are potential times in the sea waters of Kintap Subdistrict, Tanah Laut District. Processing methods digital images using Aqua Image MODIS are proven to be applicable as a method of making a fishing ground zone map. Presented on a scale of 1: 1,000,000 on A3 paper. The results of spatial measurements show that the largest area of potential fishing ground zone is in April, reaching 11,188.29 Km2